Devising a method for building an educational project team based on the analysis of competency matrix - Biloshchytskyi, Andrii; Gladka, Myroslava; Kuchanskyi, Oleksandr; Andrashko, Yurii; Faizullin, Adil (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the processes to form teams for educational projects. The issue addressed is the distribution of lecturers based on educational components, taking into account the complex set of functional requirements for the executors of specific educational projects. To successfully implement educational projects, it is proposed to build a reserve of personnel and form effective teams of performers who have the necessary competencies and experience in implementing international projects. A method for determining the individual competencies of executors of educational projects at institutions of higher education has been formalized. It is proposed to evaluate lecturers on the basis of their effectiveness in teaching educational components, which is measured by testing the level of assimilation of program results by students. As a result, a matrix of competences was constructed, containing the evaluations of performers, which helps the management of the institution to make decisions about the extension or termination of contracts with lecturers, as well as possible bonuses. A method for analyzing the matrix of competencies for the formation of an educational project team is to identify lecturers who have the necessary competencies to provide educational components. As a result of applying the method, a project team is formed, which is able to provide all the necessary competencies, taking into account the qualification requirements. The method helps determine the shortage of qualified personnel and the need for their development. The method was verified using an example of an educational project in Kazakhstan to form a team of lecturers that meets the qualification requirements of the educational program. The results show that even a minimum team of three people can provide all 16 competencies at an appropriate level, and the involvement of additional performers expands the possibilities of flexible distribution of responsibilities between them